The occurrence of tumors of the central nervous system in the state of Sergipe from 2008 to 2017 (Research, Society and Development, 2020)
Objectives: The main objective of the study is to determine the epidemiological profile of patients with CNS tumor in the State of Sergipe from 2008 to 2017 and through the results allow to understand its prevalence and the main types of these tumors in Sergipe, comparing the results with other Brazilian states and other countries and assisting future research regarding this thematic. Methods: This is a retrospective cross-sectional study that initially included 215 patients - who were later restricted to 132 - diagnosed with brain tumors. These data were tabulated and statistically analyzed using IBM® SPSS Statistics® 24 and Microsoft® Excel® 2016 and then correlated. Results: The highest prevalence of CNS tumors was found in female patients, adults (mainly between 51 and 70 years old), Afro-Americans and married individuals. The largest amount of cases was found through the years 2014 and 2015. The most prevalent type of tumor in this study was glioma, followed by meningioma. Conclusion: This research evaluated whether social demographic factors of the CNS tumors patients in Sergipe were comparable to the literature. Our findings were similar to previus published data, with the exception of race and sex, as the prevalence varied accordingly to local populations in each study. The autors believe this study may constitute a foundation for future epidemiological studies in this topic.